COVID-19 and its implication for obstetrics and gynaecology practice in Africa. (2021)
Having to cope with corona virus disease 2019 (COVID-19) is likely to create imbalances in health care provision in the obstetrics and gynecology practices in Africa where most countries still battle with high rate of maternal morbidities and mortalities as well as poor or inadequate quality gynecological care. COVID-19 has spread to the continents of the world including all African nations since it was first reported in Wuhan, China in December 2019. Its impact and implications on the obstetrics and gynecology practice in Africa are yet to be fully explored. Routine essential services are being disrupted; therefore, giving rise to the need to redeploy the already limited health personnel across health services in Africa. This is an attempt to discuss the potential implications for obstetrics and gynaecologic practice in Africa.